Assessment of Glycometabolism Impairment and Glucose Variability Using Flash Glucose Monitoring System in Patients With Adrenal Diseases - Han, Minmin; Cao, Xiaoming; Zhao, Changjian; Yang, Luyang; Yin, Nan; Shen, Pengliang; Zhang, Jin; Gao, Fei; Ren, Yi; Liang, Dong; Yang, Jing; Zhang, Yi; et al. (Frontiers in Endocrinology, 2020)
Background This study aimed to investigate the characteristics and extent of glycometabolism impairment in patients with adrenal diseases, including Cushing syndrome, primary aldosteronism, pheochromocytoma, and nonfunctional adrenal incidentaloma. Methods This study enrolled thirty-two patients with adrenal diseases as adrenal disease groups and eight healthy individuals as healthy controls. Blood glucose levels were indicated by glucose concentration in interstitial fluid, which was documented using flash glucose monitoring system. According to flash glucose monitoring system data, parameters representing general blood glucose alterations, within-day and day-to-day glucose variability, and glucose-target-rate were calculated. Furthermore, blood glucose levels at nocturnal, fasting, and postprandial periods were analyzed. Besides, islet β-cell function and insulin resistance were assessed. Results Analysis of flash glucose monitoring system-related parameters indicated impaired glycometabolism in patients with adrenal diseases compared with that of healthy controls at general blood glucose, within-day and day-to-day glucose variability, and glucose-target-rate levels. Furthermore, the dynamic glucose monitoring data revealed that significantly affected blood glucose levels compared with that of healthy controls were observed at postprandial periods in the Cushing syndrome and primary aldosteronism groups; at nocturnal, fasting and postprandial periods in the pheochromocytoma group. Significant insulin resistance and abnormal β-cell function were observed in the Cushing syndrome group compared with that in healthy controls. Conclusion Adrenal diseases can negatively affect glucose metabolism. Patients diagnosed with adrenal diseases should receive timely and appropriate treatment to avoid adverse cardiovascular events linked to hyperglycemia and insulin resistance.